Suppressive Effects of Hot-water Extract of Magnolia obovata on Clostridium perfringens Enterotoxin-induced Cytotoxicity in Human Intestinal Caco-2 Cells - Kawahara, Takeshi; Fujii, Kotomi; Nakajima, Kouki; Fujii, Rikuri; Inagaki, Shuichiro; Hara, Kunio; Yasui, Hisako (Planta Medica, 2020)
The physiological functions of the leaves of Japanese big-leaf magnolia (Magnolia obovata) against enterotoxins produced by foodborne pathogens remain unclear. In this study, we evaluated the protective effects of M. obovata leaf extract (MLE) against the cytotoxicity of Clostridium perfringens enterotoxin (CPE), which causes the symptoms of C. perfringens type A food poisoning. The protective effects of MLE against CPE-induced cytotoxicity were evaluated in human intestinal epithelial Caco-2 cells. Pre-treatment with MLE significantly suppressed the cytotoxicity induced by CPE in undifferentiated and differentiated human intestinal Caco-2 cells at a pH range of 4.0 – 7.0. This CPE-suppressive effect was due to a hydrophilic sugar-containing compound without phenolic and protein structures but not the hydrophobic biologically active neolignans, honokiol and magnolol. MLE had a protective effect against cytotoxicity caused by type A C. perfringens. Our results provide novel insight regarding the usage of M. obovata in managing food poisoning.
Keywords: Magnolia obovata; Magnoliaceae; Clostridium perfringens; enterotoxin; food poisoning; claudin